Diagnosis, monitoring and prognosis of secondary brain damage in icu patients with traumatic brain injuries - Karipiadou, Aikaterini; Korfias, Stefanos; Papastavrou, Evridikh (Health & Research Journal, 2018)
Traumatic brain injury (TBI) is the brain injury that occurs whenever a physical force that impacts the head leads to neuropathology. The types of primary TBI are penentrating TBI or non-penetrating TBI and it can lead to intracerebral contusions, hemorrhages or extra-axial hematomas. Patients with TBI can also have skull fractures or concussions. The injury severity can be classified in many ways but the most established and common used is the Glascow Coma Scale (GCS). However, with the GCS, each of the severity criteria has limitations and might mot be an accurate predictor of TBI severity and outcome when used alone. For this reason it is often used in conjunction with other parameters (Abbreviated Injury Scale - AIS). Secondary Brain Damage is the injury that occurs to the TBI patient not at the time of the accident, but during the following minutes, hours or days. There are many mechanisms that lead to development of cerebral edema, blood-brain barrier disruption, vasospasm, increase in volume of bleeding, contusions and intracranial hypertension. These mechanisms can act either in cellular level or systemic level. The cellular mechanisms that lead to secondary brain damage include necrosis or apoptosis, mitochondrial dysfunction, excitotoxicicty, formation of free radicals, changes in cerebral glucose metabolism and inflammation. The mechanisms at systemic level include hypoxia-cerebral oxygenation, hypo or hypertension, hypo or hyper-capnia, anemia, hyponatremia and hyper or hypoglycemia. The first tool to diagnose severe TBI and secondary brain injury is neurological assessment. Neuroimaging is one of the most important ways for diagnosis. Computed Tomography (CT scan), Magnetic Resonance Imaging (MRI), cerebral angiography, transcranial Doppler, CT perfusion, Xenon CT, MRI diffusion, MRI perfusion, MRI spectrometry and Positron Emission Tomography (PET) are possible ways of imaging that not only help in the diagnosis but give important information that help in choosing the correct management. Moreover, neuromonitoring, helps in the correct management of the patient.